The impact of the cost-of-living crisis on European households - Boris Chafwehé; Mattia Ricci; Daniel Stöhlker (European Commission, Joint Research Centre (JRC), 2024)
We study the impact of the recent cost-of-living crisis on European households using detailed data on individual consumption, income and wealth. We account for the various channels through which inflation affects individual households, and for the monetary and fiscal policy responses to the inflationary shock. Our results indicate that the effects of inflation through the revaluation of nominal wealth and income are one order of magnitude larger than the effect arising from differences in individual consumption patterns. On average, the effect of inflation is regressive, with lower income households suffering the biggest losses. Among population subgroups, young individuals and households with mortgage debt are the biggest winners of the inflation surge, while older individuals with large nominal net savings positions are the main losers. Fiscal policy measures, especially those targeted towards low-income households, were successful in dampening the negative and regressive impact of inflation.
Keywords: G51; D31; E31; 330; Inflation Heterogeneity; Monetary and Fiscal Policy; Euro Area